THE INFLUENCE OF HEALTH PROMOTION USING POSTER MEDIA ON STUDENTS' KNOWLEDGE AND ATTITUDES ABOUT HEALTHY FOOD AT SHANTO THOMAS 2 ELEMENTARY SCHOOL, MEDAN CITY IN 2024" - Liarosa Veronika Sinaga; Buulolo, Sitimawar; Jasmen manurung; Seri Asnawati Munthe (TOUR HEALTH JOURNAL, 2024)
Purpose:Snacks are food and drinks processed by food craftsmen at the point of sale or served as ready-to-eat food that will be sold to the public. The importance of information about snacks because children often consume snacks and parents and children's knowledge about healthy snacks is still lacking. Snacks function as the main food or snacks for children and nutritional intake for children. The general objective of the study was to determine the effect of health promotion using poster media on students' knowledge and attitudes about healthy snacks at SD Shanto Thomas 2 Medan City in 2024. Method: This study uses a quantitative Method. This type of research is a quasi experiment where the design form used is one group pre-test and post-test. This research will be conducted at SD Shanto Thomas 2 Medan City. The sample in this study used the total population technique in SD Shanto Thomas 2 Medan City as many as 102 people. The research variables are knowledge and attitude Results: The results showed that the average knowledge of students before being given health promotion using poster media was 3.49 with a standard deviation of .992, while the average knowledge of students after being given health promotion using poster media about healthy snacks was 9.45 with a standard deviation of 726. The difference in the average knowledge of students before and after being given health promotion was 5.62. while after being given health promotion the average knowledge value became 9.45. The results of the study showed that the average attitude of students before being given health promotion using poster media about healthy snacks was 6.00 with a standard deviation of 1.024, while the average attitude of students after being given health promotion through poster media about healthy snacks was 9.11 with a standard deviation of 673. Disscusion and Conclusion: The difference in the average attitude of students before and after being given health promotion was 3.11. While after being given health promotion, the average attitude value of students was 6.00 to 9.11 after being given health promotion through poster media and it is expected that health promotion about snacks with the poster method will still be given.